Antibody cross-linking of human platelet P-selectin induces calcium entry by a mechanism dependent upon Fcγ receptor IIA - Sathish, Jean G.; Falati, Shahrokh; Croce, Kevin; Crump, Colin; Furie, Barbara C.; Furie, Bruce; Poole, Alastair W. (Thrombosis and Haemostasis, 2004)
It is established that antibody-induced cross-linking of platelet surface receptors is able to activate platelets in a manner dependent upon FcγRIIA. This has not, however, previously been shown for the adhesion receptor P-selectin, and since there is evidence that P-selectin may couple to activation events, it was important to address whether antibody cross-linking of this receptor induced signalling events, and whether this was dependent on FcγRIIA. Here we show that although addition of soluble P-selectin ligand rPSGL-Ig alone is not able to induce calcium signalling, further addition of a full-length rabbit antihuman IgG leads to a sustained rise in [Ca2+]i.This was due to an increase in the frequency and amplitude of transient calcium spiking in single platelets. The response was dependent upon engagement of both P-selectin and FcγRIIA since blocking antibodies to either receptor inhibited the response. The calcium rise is mediated primarily by induction of a calcium entry mechanism involving the Na+-Ca2+ exchanger operating in reverse mode, since it was blocked by inhibitors of Na+-Ca2+ exchange, bepridil and 5 mM NiCl2.
Keywords: P-selectin; FcγRIIA; calcium; rPSGL-Ig; platelet